Evidence of SARS-CoV-2 in nasal brushings and olfactory mucosa biopsies of COVID-19 patients - Pipolo, Carlotta; Bottai, Daniele; Fuccillo, Emanuela; Aronica, Eleonora; Bruschi, Fabio; Bulfamante, Antonio Mario; Castellani, Luca; Canevini, Maria Paola; Chiumello, Davide; Ferrari, Sergio; Martinelli, Carla; Muttini, Stefano; et al. (PloS one, 2022)
The aim of the present study is to detect the presence of SARS-CoV-2 of patients affected by COVID-19 in olfactory mucosa (OM), sampled with nasal brushing (NB) and biopsy, and to assess whether a non-invasive procedure, such as NB, might be used as a large-scale procedure for demonstrating SARS-CoV-2 presence in olfactory neuroepithelium. Nasal brushings obtained from all the COVID-19 patients resulted positive to SARS-CoV-2 immunocytochemistry while controls were negative. Double immunofluorescence showed that SARS-CoV-2 positive cells included supporting cells as well as olfactory neurons and basal cells. OM biopsies showed an uneven distribution of SARS-CoV-2 positivity along the olfactory neuroepithelium, while OM from controls were negative. SARS-CoV-2 was distinctively found in sustentacular cells, olfactory neurons, and basal cells, supporting what was observed in NB. Ultrastructural analysis of OM biopsies showed SARS-CoV-2 viral particles in the cytoplasm of sustentacular cells. This study shows the presence of SARS-CoV-2 at the level of the olfactory neuroepithelium in patients affected by COVID-19. For the first time, we used NB as a rapid non-invasive tool for assessing a potential neuroinvasion by SARS-CoV-2 infection.